Transnational Governance and the Reduction of Inequality within and between Countries (Global Journal of Human-Social Science, 2024)
The object under discussion is transnational governance as a tool for identifying and reducing inequality, in accordance with Sustainable Development Goal 10, which aims to reduce inequality within and among countries. The overall objective is to analyze to what extent transnational governance can contribute to the identification of vulnerable groups and, as a consequence, to enable transnational actors to cooperatively design actions to reduce inequality among peoples. Transnational governance can be understood as the reordering processes that the world has been going through, where various relations between the local and the global evolve at the same time, within and across borders. It was found that it is possible to point out that transnational governance aligned with the Sustainable Development Goals can indeed be considered an effective tool for reducing inequalities, both internally within and between countries, and that it can guarantee equity, justice, and uniformity for individuals who have equal rights and opportunities. The methodology is based on a qualitative and quantitative approach, and can also be classified, according to its objectives, as descriptive and prescriptive. The research technique will be bibliographic analysis.
Keywords: transnational governance social inequality SDG 10 justice vulnerable groups